Antimicrobial activity of phenolics and glucosinolate hydrolysis products and their synergy with streptomycin against pathogenic bacteria - Maria J. Saavedra (2010)
The purpose of the present study was to evaluate the in vitro antibacterial effects of different classes of important and common dietary phytochemicals (5 simple phenolics - tyrosol, gallic acid, caffeic acid, ferulic acid, and chlorogenic acid; chalcone - phloridzin; flavan-3-ol - (-) epicatechin; seco-iridoid - oleuropein glucoside; 3 glucosinolate hydrolysis products - allylisothiocyanate, benzylisothiocyanate and 2-phenylethylisothiocyanate) against Escherichia coli, Pseudomonas aeruginosa, Listeria monocytogenes and Staphylococcus aureus. Another objective of this study was to evaluate the effects of dual combinations of streptomycin with the different phytochemicals on antibacterial activity. A disc diffusion assay was used to evaluate the antibacterial activity of the phytochemicals and 3 standard antibiotics (ciprofloxacin, gentamicin and streptomycin) against the four bacteria. The antimicrobial activity of single compounds and dual combinations (streptomycin-phytochemicals) were quantitatively assessed by measuring the inhibitory halos. The results showed that all of the isothiocyanates had significant antimicrobial activities, while the phenolics were much less efficient. No antimicrobial activity was observed with phloridzin. In general P. aeruginosa was the most sensitive microorganism and L. monocytogenes the most resistant. The application of dual combinations demonstrated synergy between streptomycin and gallic acid, ferulic acid, chlorogenic acid, allylisothiocyanate and 2-phenylethylisothiocyanate against the Gram-negative bacteria. In conclusion, phytochemical products and more specifically the isothiocyanates were effective inhibitors of the in vitro growth of the Gram-negative and Gram-positive pathogenic bacteria. Moreover, they can act synergistically with less efficient antibiotics to control bacterial growth.